Comparative Analysis of Sundanese and Indonesian “Ngalogat” Syntactic Semiotic Usage in Classical Arabic Texts Translation - Syabani, Gina Purnama; Al Farisi, Mohamad Zaka; Supriadi, Rinaldi (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
Translating texts between languages is a complex practice, especially in maintaining the accuracy, clarity, and naturalness of the original text. One of the translation methods used in many traditional Islamic boarding schools and still existing today is ngalogat, a method that uses syntactic symbols in the translation process. This research aims to examine and compare the use of syntactic symbols in the Arabic-Sundanese ngalogat and the Arabic-Indonesian ngalogat in translating the yellow book. The research method used is comparative analysis with a qualitative descriptive approach. Syntactic symbols are identified based on Saussure's semiotic theory. The object of this research is selected sentences from the book Al-Ājurrūmiyyah, which includes the syntactic functions of Arabic. Data triangulation techniques were used as data analysis in this research by collecting data through observation, document analysis, and in-depth interviews. Data was collected and obtained using the listening and note-taking method, involving 10 participants who were selected purposively as research subjects. Data in the form of documents was then analyzed to see the comparison of the use of syntactic symbols in the Arabic-Sundanese ngalogat and Arabic-Indonesian ngalogat methods. The results of the research show several similarities, differences, advantages, and disadvantages between the Arabic-Sundanese ngalogat and Arabic-Indonesian ngalogat, which are presented in table format. Abstrak Penerjemahan teks antarbahasa merupakan sebuah praktik yang kompleks, terutama dalam mempertahankan akurasi, kejelasan, dan kenaturalan dari teks asli. Salah satu metode penerjemahan yang digunakan di banyak pesantren tradisional dan masih eksis sampai saat ini ialah ngalogat, sebuah metode yang menyuratkan simbol-simbol sintaksis dalam proses penerjemahannya. Penelitian ini bertujuan untuk mengkaji dan membandingkan penggunaan simbol-simbol sintaksis ngalogat Arab-Sunda dan ngalogat Arab-Indonesia dalam menerjemahkan kitab kuning. Metode penelitian yang digunakan ialah analisis komparatif dengan pendekatan deskriptif kualitatif. Simbol-simbol sintaksis ngalogat diidentifikasi berdasarkan teori semiotika Saussure. Objek penelitian ini ialah kalimat-kalimat terpilih dari kitab Al-Ājurrūmiyyah yang mencakup fungsi-fungsi sintaksis bahasa Arab. Teknik triangulasi data digunakan sebagai analisis data dalam penelitian ini dengan mengumpulkan data melalui observasi, analisis dokumen, dan wawancara mendalam. Data dikumpulkan dan diperoleh melalui metode simak dan catat, dan melibatkan 10 partisipan yang dipilih secara purposive sebagai subjek penelitian. Data berupa dokumen kemudian dianalisis untuk melihat perbandingan penggunaan simbol-simbol sintaksis dalam metode ngalogat Arab-Sunda dan ngalogat Arab-Indonesia. Hasil penelitian menunjukkan beberapa persamaan, perbedaan, kelebihan, dan kekurangan di antara ngalogat Arab-Sunda dan ngalogat Arab-Indonesia yang dipresentasikan dalam format tabel.